What Happens When Agent T Gets a Computer? The Labor Market Impact of Cost Efficient Computer Adoption - Lex Borghans; Bas ter Weel (Institute for the Study of Labor (IZA), 2003)
This paper offers a model to explain how computer technology has changed the labor market. It demonstrates that wage differentials between computer users and non-users are consistent with the fact that computers are first introduced in high-wage jobs because of cost efficiency. Furthermore, skill upgrading occurs because of a reemphasis on non-routine tasks after computer adoption. The model also reveals that neither differences in computer skills nor complementary skills are needed to explain wage differentials between computer users and non-users, skill upgrading, and the changing organization and intensity of work. Finally, the predicted effects on the wage structure following the diffusion of computers are consistent with the empirical evidence.
Keywords: O33; J31; J30; 330; wage differentials by skill; computer use and skill; Computergestütztes Verfahren; PC (Personal Computer); Arbeitsnachfrage; Qualifikation; Kostenfunktion; Weiterbildung; Innovationsdiffusion; Theorie